The Beginning of Islamic Architecture and Its Impact To Indian And Central Asian Architecture - Laziz Rahimov PhD; Datin Seri Ar Dr Norwina Mohd Nawawi; Maxmatqulov Ilhom PhD; Dilshod Luqmonov; Kholdorova Dilrabo; Kamilova Marjona (Genius Journals, 2023)
In given article we will try to analyze of Islamic architecture and it`s evolution process. Moreover, we will try to clear up the role of Islamic architecture in formation Central Asian and Indian architecture. Lastly, we describe how Islamic buildings has been created and its development over the years, also, we have given evidence supporting our points.
Keywords: Islamic architecture; Architecture of masjid